(untitled) (Географический вестник=Geographical bulletin, 2017)
Освещается вклад представителей географического образования и науки Пермского края в достижение победы в Великой Отечественной войне, в том числе студентов и преподавателей географических факультетов Пермского государственного педагогического института и Пермского государственного университета – участников боевых действий и работавших в тылу. GEOGRAPHICAL RESEARCHES AND EDUCATION DURING THE GREAT PATRIOTIC WAR (ON MATERIALS OF PERM REGION) The impact of the representatives ofPermregion’s geographical education and science for the achievement of the Victory in The Great Patriotic War is revealed. It is told about students and lecturers of the geographical departments of Perm State Pedagogical Institute andPermStateUniversity, who took part in warfare and worked in the difficult conditions of rearward.